Global University Rankings and the Politics of Knowledge - Stack, Michelle (University of Toronto Press, 2021)
For many institutions, to ignore your university's ranking is to become invisible, a risky proposition in a competitive search for funding. But rankings tell us little if anything about the education, scholarship, or engagement with communities offered by a university. Drawing on a range of research and inquiry-based methods, Global University Rankings and the Politics of Knowledge exposes how universities became servants to the education industry and its impact. Conceptually unique in its scope, Global University Rankings and the Politics of Knowledge addresses the lack of empirical research behind university and journal ranking systems. Chapters from internationally recognized scholars in decolonial studies provide readers with robust frameworks to understand the intersections of coloniality and Indigeneity and how they play out in higher education. Contributions from diverse geographical and disciplinary contexts explore the political economy of rankings within the contexts of the Global North and South, and examine alternatives to media-driven rankings. This book allows readers to consider the intersections of power and knowledge within the wider contexts of politics, culture, and the economy, to explore how assumptions about gender, social class, sexuality, and race underpin the meanings attached to rankings, and to imagine a future that confronts and challenges cognitive, environmental, and social injustice.